Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1021/jacsau.2c00214
|View full text |Cite
|
Sign up to set email alerts
|

Dispersive 2D Triptycene-Based Crystalline Polymers: Influence of Regioisomerism on Crystallinity and Morphology

Abstract: The merging of good crystallinity and high dispersibility into two-dimensional (2D) layered crystalline polymers (CPs) still represents a challenge because a high crystallinity is often accompanied by intimate interlayer interactions that are detrimental to the material processibility. We herein report a strategy to address this dilemma using rationally designed three-dimensional (3D) monomers and regioisomerism-based morphology control. The as-synthesized CPs possess layered 2D structures, where the assembly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The SEM images conclude that the optimized condition for polymerization is less rigorous, i.e., to stir the resultant reaction mixture at room temperature for 30 min. The predominance of bowl shape in the case of OPN-5 may stem from the extended π surface of THBPB , which further elevates the π–π stacking interaction during closing the polymer ends within a close proximity. , The SEM images also revealed that the average morphological size of OPN-5 was significantly smaller as compared to OPN-4 . It can be assumed that, since the arms of the OPN-5 precursor are larger, a smaller number of these precursors were able to produce a sphere, but these many precursor units of OPN-4 were unable to make a sphere after linked by the phosphate units.…”
Section: Results and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The SEM images conclude that the optimized condition for polymerization is less rigorous, i.e., to stir the resultant reaction mixture at room temperature for 30 min. The predominance of bowl shape in the case of OPN-5 may stem from the extended π surface of THBPB , which further elevates the π–π stacking interaction during closing the polymer ends within a close proximity. , The SEM images also revealed that the average morphological size of OPN-5 was significantly smaller as compared to OPN-4 . It can be assumed that, since the arms of the OPN-5 precursor are larger, a smaller number of these precursors were able to produce a sphere, but these many precursor units of OPN-4 were unable to make a sphere after linked by the phosphate units.…”
Section: Results and Discussionmentioning
confidence: 96%
“…The PdNP loading in OPN-5 reached as high as 36.46%, whereas Pd@OPN-4 could load only 12.46% (Figure S6). ,,, Therefore, the increase in the PdNP loading from Pd@OPN-4 to Pd@OPN-5 indicates that the bowl-shaped morphology can load PdNPs to a much greater extent as compared to the spherical morphology.…”
Section: Results and Discussionmentioning
confidence: 99%
“…With respect to other synthetic procedures for TAPB-OHPDA COF powders (Fig. 3d), 25,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] the results from this work clearly show that the implementation of flow chemistry allows for rapid conversion to crystalline material, reducing the standard 72-hour synthesis time by more than 36× for the same quality, or better. To further demonstrate generalizability, this method was extended to the synthesis of TAPB-PDA COF, which is derived from 1,3,5-tris(4aminophenyl)benzene and terephthalaldehyde (PDA).…”
mentioning
confidence: 86%
“…Furthermore, the C–H bonds in the triptycene ligand were oriented out of the plane. These features suppress interlayer interactions . Although several syntheses of two-dimensional triptycene-bridged coordination polymers possessing various functionalities originating from planar coordination geometries and electrochemical activities have been reported, to the best of our knowledge, only one publication has reported the synthesis of triptycene-bridged coordination polymers composed of bis­(diimino)metal complexes in powder form .…”
Section: Introductionmentioning
confidence: 99%